Digital Authoritarianism: Protecting Islam in Multireligious Malaysia - Syaza Shukri (Religions, 2023)
Mahathir Mohamad’s autocratic leadership over Malaysia for decades has left the country with a reputation for being, at best, a hybrid system. The country witnessed the rise of the internet during Mahathir’s first term as prime minister, which led to the establishment of the Malaysian Communications and Multimedia Commission (MCMC) in 1998 to oversee telecommunications and the internet within the country. Since then, the MCMC has overseen the removal of inflammatory content from the internet. The Malaysian government has emphasised its commitment to purging the internet of harmful content including pornography, gambling, and offensive teachings about Islam in the name of safeguarding the religion and its adherents. Since the 1980s, Islam has been institutionalised in Malaysia, and the government has also used the faith as rationale for policing online behaviour especially on the 3R—religion, race, and royalty. With the cover of religious rhetoric like preventing “fitnah,” or social upheaval, the government has used Islam to legitimise its activities in curtailing free expression online, including criticism of the government. Recently, Islam has also been utilised by populist actors in their online posting with little repercussions. This article explains the methods by which the Malaysian government has attempted to limit web access using religious discourse as justification. Since Malaysia has a Muslim majority, such restrictions can be justified in the name of Islam at the expense of the minorities.